Analisa Karakteristik Visual dan Strategi Visual Iklan Wall Painting: Studi Kasus Iklan Wall Painting Empat Operator Telekomunikasi Nasional - Gema Arifrahara; Naomi Haswanto; Deddy Wahjudi (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Advertising billboards is outdoor media conventional, but currently there are phenomena advertising by utilizing wall house or store in a public hall in town. Utilization wall as advertisement media is approach alternative against outdoor advertising at the research is done. The purpose of this research is to know about development advertising wall painting based on characteristic and strategies the visuals on the media. Method research used writer is descriptive analysis in finding and develop object research with the adoption of data via process interview observation and a questionnaire interview structure. Parameters research reviewed based on aspects characteristic visual contained in object radiotelegraphy; tataletak, color, logo, typography, texture, and graphics groundswell. Aspect strategy visual radiotelegraphy; visualization coquet; attached in memory, strengthen trust, maintain attention, and form Attached in memory, strengthen trust, maintain attention, and forming association. Characteristic of visual and strategy visual advertising wall painting show the form visualizations simple. Logo and color is most important element make advertising now that can work effective. Notch advertising wall painting in the series of processes of communication advertising is as an advertisement amplifier and reminder that becomes a fastener of the series a promotion is there.